2019
DOI: 10.1039/c9ra04299g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of counter-ions on the properties and performance of non-conjugated polyelectrolyte interlayers in solar cell and transistor devices

Abstract: Non-conjugated polyelectrolytes are empolyed as interfacial layers at the electrodes of solar cells and transistor devices to improve the power conversion efficiency (PCE) and device performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Polymers 2020, 12, x FOR PEER REVIEW 6 of 10 consistent with nitrogen in a tertiary organic amine bonding state, which was expected to be the predominant bonding state in the PEIE backbone [38]. Previous NMR studies of the materials confirmed the degree of functionalization in the backbone (nitrogen quaternization) of this series of polyelectrolytes [39]. Figure 3d-f corresponds to photoelectron emission bands of Pb at 138.7 eV from all films, consistent with the +2 oxidation state in this metal.…”
Section: Resultsmentioning
confidence: 67%
“…Polymers 2020, 12, x FOR PEER REVIEW 6 of 10 consistent with nitrogen in a tertiary organic amine bonding state, which was expected to be the predominant bonding state in the PEIE backbone [38]. Previous NMR studies of the materials confirmed the degree of functionalization in the backbone (nitrogen quaternization) of this series of polyelectrolytes [39]. Figure 3d-f corresponds to photoelectron emission bands of Pb at 138.7 eV from all films, consistent with the +2 oxidation state in this metal.…”
Section: Resultsmentioning
confidence: 67%
“…Device with PFBP–I as ETM showed a slightly lower PCE of 15.22% due to its lower solubility in polar solvents, which prevents the formation of high‐quality thin‐film upon active layer. [ 71 ] Devices with PFBP–BArF 4 as ETM showed poor performance (10.53%), which can be explained by the mismatch of energy alignments in the cathode. The external quantum efficiencies (EQEs) for devices with CPEs were also conducted and the integration of EQE curves (Figure 4b) confirmed the J sc output in photovoltaic devices.…”
Section: Resultsmentioning
confidence: 99%
“…Do et al noted comparable trends when using cationic polyelectrolytes based on viologens that comprise various sizes of the anion. 20,45 It should be noted that the J sc improvement was most important for the device with NDIN-I. A typical shift from a Schottky to an ohmic contact is suggested by an increase in J sc .…”
Section: Interfacial Properties Of Ito Modified With Smsmentioning
confidence: 99%